A NEW AMORPHOPHALLUS FROM THAILAND - LARSEN, KAI; LARSEN, S. SAKSUWAN (REINWARDTIA, 1974)
AmorpknphoMus dixenii is described and illustrated; this new species is assigned to section Cimdaritm and key to Asiatic species of this section is presented. Chromosome number of this species is found to be 2n =28.